2002
DOI: 10.1007/s001980200056
|View full text |Cite
|
Sign up to set email alerts
|

Normal Vertebral Body Dimensions: A New Measurement Method Using MRI

Abstract: Much clinical research on osteoporosis is aimed at documenting a reduction in vertebral fracture rates, but there is considerable disagreement about defining normality. Most methods for measuring vertebral body dimensions use lateral radiographs. In the present paper, we investigate the reliability of magnetic resonance imaging (MRI) for normal reference determination. A validation study was performed on a cadaver by comparing vertebral body volume measured both with MRI (sagittal acquisition in T1 weighted se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The volume of the cavity, inclusive of the interface elements, was 13.4% of the total volume of the vertebral body, which is comparable with the reported proportional filling of vertebral bodies with bone cement. 25,41,42 Material and element properties (ie, thickness of shells) were extracted from the published studies for bone (endplate, cancellous, and cortical), degenerated disc, and bone cement. The material properties, thickness of shells (where applicable), and types of elements are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The volume of the cavity, inclusive of the interface elements, was 13.4% of the total volume of the vertebral body, which is comparable with the reported proportional filling of vertebral bodies with bone cement. 25,41,42 Material and element properties (ie, thickness of shells) were extracted from the published studies for bone (endplate, cancellous, and cortical), degenerated disc, and bone cement. The material properties, thickness of shells (where applicable), and types of elements are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…MRI studies where the dimensional accuracy was important have been reported by a number of authors [6][7][8][9][10]. Accuracy depends on numerous factors, including scanning parameters and segment size.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a note of caution, the material used for the tested phantoms is not a representation for soft tissue. Cyteval et al [21] measured vertebral body dimensions using MRI, in order to compare the MRI measurement of vertebral area and volume with direct cadaver measurements. In their study, water displacement was used for volume measurement of cadaver vertebra.…”
Section: Discussionmentioning
confidence: 99%